2020
DOI: 10.3389/fbioe.2020.579404
|View full text |Cite
|
Sign up to set email alerts
|

Development and Evaluation of Drug Loaded Regenerated Bacterial Cellulose-Based Matrices as a Potential Dosage Form

Abstract: Bacterial cellulose (BC) is a highly pure form of cellulose and possesses superior physico-mechanical properties with wide range of applications. These properties of BC can further be improved by various modifications, including its regeneration from the BC solution. In the current research work, regenerated BC (R-BC) matrices were prepared using N-methyl-morpholine-oxide (NMMO; 50% w/w solution in water) and loaded with model drugs, i.e., famotidine or tizanidine. The characterization of drug loaded regenerat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(4 citation statements)
references
References 38 publications
(103 reference statements)
0
4
0
Order By: Relevance
“…This hybrid dielectric was created from tetrakis-dimethyl-aminozirconium and 2-hydroxyethyl methacrylate-a high-k inorganic material and a soft organic material, respectively. The resulting film demonstrated a high dielectric constant, low leakage current density, and high breakdown field, indicating its suitability for advanced flexible electronic applications [11,12].…”
Section: Synthesis Methods For Cellulose-based Hybrid Filmsmentioning
confidence: 99%
“…This hybrid dielectric was created from tetrakis-dimethyl-aminozirconium and 2-hydroxyethyl methacrylate-a high-k inorganic material and a soft organic material, respectively. The resulting film demonstrated a high dielectric constant, low leakage current density, and high breakdown field, indicating its suitability for advanced flexible electronic applications [11,12].…”
Section: Synthesis Methods For Cellulose-based Hybrid Filmsmentioning
confidence: 99%
“…The obtained results revealed that immobilization of SOD on BC enhanced its stability more than 40% after incubating at higher pH levels and temperatures compared to the free SOD, which typically degraded under those conditions. Therefore, the immobilization process using BC or other substances holds the potential to improve the stability of bioactive compounds under various conditions, which is a critical factor for the labile compounds [39,41].…”
Section: Ph and Temperature Stability Of Immobilized Sodmentioning
confidence: 99%
“…NMMO treated BC is called regenerated bacterial cellulose (R-BC). R-BC has been widely implemented in drug delivery e.g it has been used for H2-blochers drugs (famotidine) and muscle relaxant (tizanidine) [ 80 ].…”
Section: Utilization Of Bacterial Cellulose/cellulose Derivative To Improve Oral/dental Drug Deliverymentioning
confidence: 99%